A PHF19-YTHDC1 condensate switches EZH2-mediated gene suppression to activation for prostate cancer progression - Shuai Yuan; Dao-Jing Ming; Jiapeng He; Meng-Yang Liu; Shao-Hua He; Hong Weng; Shu Xi; Jin-Hui Zhang; Ming-Hui Shi; Jin-Long Cui; Lu-Yao Li; Haozhe Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
EZH2, a core component of PRC2 complex, silences global gene expression by tri-methylating histone H3K27. It remains an elusive question that EZH2 hyperexpression discords with its H3K27me3 activity of gene suppression in advanced prostate cancer. Here, we report a nascent RNA-dependent PHF19-YTHDC1 condensate capable of switching EZH2-mediated gene suppression to activation during prostate cancer progression. We found that the long isoform of PRC2 accessory subunit PHF19, PHF19L, was highly expressed in advanced prostate cancer that promoted the tumor progression and hormonal therapy resistance. Mechanistically, PHF19L was recruited to the m 6 A modified nascent RNA through YTHDC1 and formed a liquid-like YTHDC1-PHF19L condensate that pulled the EZH2 away from chromatin, resulting in reduced H3K27me3 deposition and the activated expression of EZH2-repressed genes. Therefore, our study reveals a biomolecular condensate that modulates the switch from EZH2-mediated epigenetic gene silence to activation during the progression of prostate cancer.